Policy engagement report: Institutionalizing multifunctional landscapes in Mbire District, Zimbabwe - Matangi, Dorcas; Nohayi, Ngowenani; Ngoma, Hambulo (CIMMYT, 2025)
This report presents the outcomes of a district-level policy engagement held in Mbire District, Zimbabwe, under the CGIAR Multifunctional Landscapes (MFL) Program within Area of Work 4: Institutions and Policies. The engagement sought to identify practical mechanisms for embedding MFL principles into local governance systems, particularly District Development Plans (DDPs), by-laws, and coordination platforms. The meeting brought together the Mbire Rural District Council (RDC), the District Development Coordinator’s Office, sectoral departments (EMA, Forestry Commission, Parks and Wildlife, ARDAS, ZINWA), traditional leaders, community representatives, and development partners including CIMMYT, DanChurchAid, and Fambidzanayi. The engagement established a shared understanding of the MFL approach-an integrated framework promoting balance between agricultural production, conservation, and human well-being-and analyzed the alignment of district policies and by-laws with national frameworks such as the Environmental Management Act (Chapter 20:27), Forest Act, Parks and Wildlife Management Act, National Wetlands Policy (2022), and the National Agricultural Policy Framework (2018-2030). Participants acknowledged that while these policies exist, implementation remains fragmented due to overlapping mandates, limited enforcement capacity, and inadequate coordination. Two thematic groups deliberated on (i) Natural Resources Management and By-laws, and (ii) Cross-Cutting Enablers covering policy alignment, gender and inclusion, capacity, and financing. Key outcomes included calls to harmonize and update local by-laws; strengthen the Mbire Natural Resources Management Platform for intersectoral coordination; expand investment in water infrastructure and irrigation; integrate modern technologies such as drones for environmental monitoring; and establish incentive systems rewarding conservation and sustainable practices. The discussions also emphasized inclusive participation of women, youth, and marginalized groups, as well as the introduction of livestock insurance and local processing industries to link conservation with livelihoods. The engagement demonstrated how district-level participatory governance can operationalize the MFL Program’s objectives, contributing directly to Output 4.1 (co-developed policy options and enacting strategies) and Output 4.3 (governance and coordination mechanisms). It reinforced that institutionalizing MFL is not a legislative event, but an adaptive process anchored in local planning cycles, inclusive decision making, and practical livelihood incentives that make sustainability attainable for communities.